Using Songs And Puppets To Increase Students’ Ability In Fluency And Involvement In English Speaking - Fitriani, Fitriani (WAHANA, 2015)
English Songs and Puppets are choosen in this research as teaching media in learning process. The goals are to increase self-confidence, fluency and involvement in English speaking at seventh grade students of Junior high school in Muara Wahau East Kalimantan. The problem faced by the students in this reseach are that most of them are not brave in speaking even in the class or outside class; They have low self-confidence and it makes them does not actively involve in teaching and learning process especially in speaking. Therefore, songs and puppets have been use to solve these problem. The purpose of this research is to describe how is students’ fluency in speaking English when self-confidence is increased by teaching English using songs and puppets and to explain how is students’ involvement on speaking in the classroom activities when using songs and puppets. This research was conducted in one cycle consisted of four meetings. Songs were implemented in the first meeting and the third meeting while puppets were implemented in the second and the fourth meeting. This research is a classroom action research. The researcher taught in the classroom while the collaborator became an observer. The collaborator collected the data in teaching and learning process by using field note and observation checklist. Students’ speaking performance were also recorded for describing their fluency. The findings show that the use of songs and puppets in the classroom could increase students’ confidence, fluency and involvement. It can be seen from their participation in the classroom, most of the students are encouraged in answering and performing. When students learnt by using songs, they enjoyed the class well and more relax. They sing while dancing followed the video song. Learning by using song can increase students’ self-confidence and made them involved actively in teaching and learning process. The repetition of song could train the students and make them pronounce the words fluently even though some of them still found difficulties in pronounciation. The use of songs and puppets in teaching and learning process could change the atmosphere in the classroom and reduce students’ fear. Most of them looked enjoying the class and made them active in speaking activities.